Impact of cable lock distribution on firearm securement after emergent mental health evaluation: a randomized controlled trial - Bijan Ketabchi; Michael A. Gittelman; Yin Zhang; Wendy J. Pomerantz (BMC, 2024)
Abstract Background Suicide-related presentations to pediatric emergency departments (PED) have increased in recent years. PED providers have the opportunity to reduce suicide risk by counseling on restricting access to lethal means. Supplementing lethal means counseling (LMC) with safety device distribution is effective in improving home safety practices. Data on PED-based LMC in high-risk patient populations is limited. The objective of this study was to determine if caregivers of children presenting to PED for mental health evaluation were more likely to secure all household firearms if given cable-style gun locks in addition to LMC. Methods In this randomized controlled trial, caregivers completed a survey regarding storage practices of firearms and medication in the home. Participants were randomized to receive LMC (control) or LMC plus 2 cable-style gun locks (intervention). Follow-up survey was distributed 1 month after encounter. Primary outcome was proportion of households reporting all household firearms secured at follow-up. Secondary outcomes included: removal of lethal means from the home, purchase of additional safety devices, use of PED-provided locks (intervention only), and acceptability of PED-based LMC. Results Two hundred participants were enrolled and randomized. Comparable portions of study groups completed follow-up surveys. Control and intervention arms had similar proportions of households reporting all firearms secured at baseline (89.9% vs. 82.2%, p = 0.209) and follow-up (97.1% vs. 98.5%, p = 0.96), respectively. Other safety behaviors such as removal of firearms (17.6% vs. 11.8%, p = 0.732), removal of medication (19.1% vs. 13.2%, p = 0.361), and purchase of additional safety devices (66.2% vs. 61.8%, p = 0.721) were also alike between the two groups. Both groups held favorable views of PED-based counseling. Within the intervention group, 70% reported use of provided locks. Preference for a different style of securement device was the most cited reason among those not using PED-provided locks. Conclusions PED-based LMC is a favorably-viewed, effective tool for improving home safety practices in families of high-risk children. Provision of cable-style gun locks did not improve rate of firearm securement compared LMC alone-likely due to high baseline rates of firearm securement and preference for different style of lock among non-utilizers. Clinical Trial Registration ID: NCT05568901 . Clinicaltrials.gov. https://clinicaltrials.gov/ . Retrospectively registered October 6, 2022. First participant enrollment: June 28, 2021.